ANALISIS TOKOH LAIL DALAM NOVEL HUJAN KARYA TERE LIYE: KAJIAN PSIKOLOGI SASTRA - Nisa Syafira Ichwan; Luqy El Dayyan; Adzkia Nisa Humaira; Mahmudah Fitriyah ZA (Universitas Hamzanwadi, 2026)
This study aims to analyze the character of Lail in the novel Hujan by Tere Liye as the center of the story’s emotional development. The scope of the study focuses on Lail’s characterization, including her role, motivations, inner conflicts, and psychological changes following a major disaster. This research employs a literary psychology approach using a qualitative descriptive method based on Nurgiyantoro’s theory of character and characterization. The literary psychology approach is used to understand Lail’s behavior, motivations, inner conflicts, and psychological development as representations of human experiences in dealing with trauma and the process of self-healing. The data consist of narrative excerpts, dialogues, and actions related to Lail, obtained from the text of the novel Hujan. The data were analyzed by describing and interpreting the character’s behavior in relation to her roles as a protagonist, antagonist, and tritagonist. The findings reveal that Lail is not only portrayed as a protagonist who represents empathy, resilience, and social concern, but also displays antagonistic and tritagonistic traits in certain situations due to emotional pressure and inner conflict. An interesting finding of this study is the complexity of Lail’s character, which realistically portrays the process of self-healing, where vulnerability and strength coexist. Through Lail’s character, the novel Hujan conveys humanitarian messages about trauma, loss, and the human ability to recover and rediscover the meaning of life.